2020
DOI: 10.1088/1681-7575/ab71b3
|View full text |Cite
|
Sign up to set email alerts
|

A validated physical model of the thermoelectric drift of Pt-Rh thermocouples above 1200 °C

Abstract: Pt and Rh oxide vapour transport is thought to dominate the thermoelectric drift of Pt-Rh thermocouples above about 1200 °C. A simple model is presented which relates the electromotive force (emf) drift rate of Pt-Rh thermoelements to the vapour pressure of Pt and Rh oxides. The model assumes that the evaporation of these oxides gives rise to a continuously changing concentration of Pt and Rh, at different rates along the length of the wires, which causes a change in the Seebeck coefficient. The model has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Note that according to (1) and (2) the cross-over temperature Measured drift rate versus calculated drift rate [11] for the thermocouples where data is available [12], showing a consistent linear relationship. Each point represents a different thermocouple composition, denoted by the composition of the two wires (e.g.…”
Section: The Modelmentioning
confidence: 74%
See 3 more Smart Citations
“…Note that according to (1) and (2) the cross-over temperature Measured drift rate versus calculated drift rate [11] for the thermocouples where data is available [12], showing a consistent linear relationship. Each point represents a different thermocouple composition, denoted by the composition of the two wires (e.g.…”
Section: The Modelmentioning
confidence: 74%
“…A simple model of Pt and Rh oxide vapour transport was recently presented [11], which predicts the influence of oxide transport to different regions of the thermocouple wire on the resulting thermoelectric stability. In this paper the model has been employed to make some predictions about the relative thermoelectric stability of different Pt-Rh alloys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In EMPRESS, a systematic investigation of a number of different Pt-Rh thermocouples showed that the most stable thermocouple consistent with readily available Pt-Rh wire compositions, at least in the temperature range 1324 °C to 1492 °C, is the Pt-40%Rh versus Pt-6%Rh thermocouple [19][20][21]. This is due to the combined effects of thermoelectric drift due to vaporisation of Pt and Rh oxides [34,35,39] A preliminary reference function was also drafted (Figure 2) [19]. In EMPRESS2, to facilitate uptake of the new thermocouple type, NMIs will systematically determine its reference function.…”
Section: Wp2: Low-drift Thermocouplesmentioning
confidence: 99%